2019
DOI: 10.3389/fmicb.2019.02450
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Contact-Dependent Growth Inhibition (CDI) System That Reduces Biofilm Formation and Host Cell Adhesion of Acinetobacter baumannii DSM30011 Strain

Abstract: Acinetobacter baumannii is a multidrug-resistant nosocomial opportunistic pathogen that is becoming a major health threat worldwide. In this study, we have focused on the A. baumannii DSM30011 strain, an environmental isolate that retains many virulence-associated traits. We found that its genome contains two loci encoding for contact-dependent growth inhibition (CDI) systems. These systems serve to kill or inhibit the growth of non-sibling bacteria by delivering toxins into the cytoplasm of target cells, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…Searching for other competition mechanisms such as the two-partner systems (Tps) already identified in strain DSM30011 ( Fig. 2 ) related to contact-dependent inhibition (CDI) ( 57 ) also resulted in negative results. These observations led us to hypothesize that the ability of strain NCIMB8209 to outcompete other bacteria was severely compromised.…”
Section: Resultsmentioning
confidence: 99%
“…Searching for other competition mechanisms such as the two-partner systems (Tps) already identified in strain DSM30011 ( Fig. 2 ) related to contact-dependent inhibition (CDI) ( 57 ) also resulted in negative results. These observations led us to hypothesize that the ability of strain NCIMB8209 to outcompete other bacteria was severely compromised.…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of studies have reported multifunctional roles for CdiA proteins, apparently independent of toxin activity. CdiA promotes adhesion on epithelial cells in A. baumannii, plays a major role in intracellular survival and intracellular escape in Neisseria meningitidis , increases the virulence of Pseudomonas aeruginosa in infection models, and controls biofilm establishment in human pathogens ( Melvin et al, 2017 ; Mercy et al, 2016 ; Pérez et al, 2016 ; Roussin et al, 2019 ; Talà et al, 2008 ). Both CDI systems investigated in our study have been shown to be constitutively active, and a secretome analysis of Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…(Burkholderia thailandensis, Burkholderia dolosa) [52][53][54][55][56][57][58][59], N. meningitidis [60], P. aeruginosa [61][62][63][64], and Acinetobacter spp. (A. baumannii, Acinetobacter baylyi) [65][66][67][68] (Table 1), while proteins similar to CdiA-CT toxin were identified also in Gram-positive species including Bacillus, Listeria, Clostridium, and Streptococcus [31]. Such proteins derived from Bacillus subtilis or Bacillus cereus and expressed in E. coli showed RNase activity and suppressed the growth of wild E. coli strains [31].…”
Section: Systems In Other Bacterial Speciesmentioning
confidence: 99%